2019
DOI: 10.1002/rnc.4644
|View full text |Cite
|
Sign up to set email alerts
|

On a method for solving a local boundary problem for a nonlinear stationary system with perturbations in the class of piecewise constant controls

Abstract: Summary The wide class of nonlinear stationary systems of ordinary differential equations taking into account restrictions on control and external perturbation is considered. An algorithm for constructing a discrete control function that guarantees the transfer of the systems from the initial state to the origin and an arbitrary neighborhood of the origin is proposed. A constructive sufficient condition of the Kalman type, in which the specified translation is possible, is obtained. The problem of robot‐manipu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…We leave the long algebra outside the scope of this paper. The complete details of the transformations can be found in [50][51][52][53], where the same idea is applied to different control problems. However, for the sake of completeness, we briefly present some derivations from the mentioned papers here.…”
Section: Auxiliary Systemmentioning
confidence: 99%
See 4 more Smart Citations
“…We leave the long algebra outside the scope of this paper. The complete details of the transformations can be found in [50][51][52][53], where the same idea is applied to different control problems. However, for the sake of completeness, we briefly present some derivations from the mentioned papers here.…”
Section: Auxiliary Systemmentioning
confidence: 99%
“…In [53], it is shown that the solution of the auxiliary system (24), closed with the auxiliary stabilizing control (30) in the domain (26), satisfies the estimate:…”
Section: Proof Of Theoremmentioning
confidence: 99%
See 3 more Smart Citations